Reflexión sobre la ciencia, el arte y la técnica (2019)
The author, as a part of an investigative plan in the esthetical studies, presents in this article a proposal for the construction of esthetic-ethic relationships that allows a new approach to the contradictions between the arts, the science and the technique, that he tries to solve. The principal conclusion highlights how these concepts explain both a material reality and a dreamed reality that explains the men life and their processes of nature transformation.